2011
DOI: 10.1167/iovs.10-7084
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Gene Expression Profiling of Retina Postintravitreal Injections of Dexamethasone and Triamcinolone at Clinically Relevant Time Points for Patient Care

Abstract: Understanding the molecular and genetic effects of intraocular steroid treatments is of clinical relevance. This in vivo study has elucidated several genes and pathways that are potentially altering the neuroprotective/neurodegenerative balance between glial and retinal ganglion cells during intravitreal steroid treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
5
1
Order By: Relevance
“…As a general observation and contrary to the data of steroid effects in the retina [ 9 ], there were far fewer genes with an altered expression at 1 month than at 1 week postinjection.…”
Section: Resultscontrasting
confidence: 88%
See 2 more Smart Citations
“…As a general observation and contrary to the data of steroid effects in the retina [ 9 ], there were far fewer genes with an altered expression at 1 month than at 1 week postinjection.…”
Section: Resultscontrasting
confidence: 88%
“…In conclusion, in our previous study [ 9 ], we have reported that intravitreal Dex and TAA resulted in gene expression changes which potentially altered the balance between neuroprotective and neurodegenerative processes in the retina. In this study, using the same mouse model, we investigated the effects of these steroids on gene expression in the RPE/choroid and found that the major influenced pathways are circadian rhythm and several neurotransmission pathways.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, we have demonstrated that our top candidate gene— Cacna2d1 —is critical for modulation of IOP in these strains. Although other positional candidates in our Chr 5 QTL, such as Nos3 and Sema3e (Supplementary Table 1 ), have been linked to glaucoma 39 – 41 , they do not fulfill our stringent selection criteria and therefore have been eliminated as candidate genes (Supplementary Table 2 ). Other positional candidates, such as Crygn and Klhl7 , have been associated with other ocular diseases 42 , 43 , but not glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…This regulation influences the expression of vascular endothelial growth factor (VEGF), inhibits pro-inflammatory genes such as tumour necrosis factor-alpha (TNF-α) and other inflammatory chemokines, and induces the expression of anti-inflammatory factors such as pigment epithelium-derived factor (PEDF). [9][10][11] Some studies show that TA, at therapeutic concentrations, significantly inhibits the expression of TNF-α, interleukin 1-beta (IL-1ÎČ), thromboxane B2 (TxB2) and leukotriene B4 (LTB4), in a dose-dependent manner. 12 Additionally, TA seems to reduce the expression of matrix metalloproteinases (MMPs) and to downregulate intercellular adhesion molecule 1 (ICAM-1) on choroidal endothelial cells.…”
mentioning
confidence: 99%